Glycogen Synthase Kinase 3α Is the Main Isoform That Regulates the Transcription Factors Nuclear Factor-Kappa B and cAMP Response Element Binding in Bovine Endothelial Cells Infected with Staphylococcus aureus - Silva-García, Octavio; Rico-Mata, Rosa; Maldonado-Pichardo, María Cristina; Bravo-Patiño, Alejandro; Valdez-Alarcón, Juan J.; Aguirre-González, Jorge; Baizabal-Aguirre, Víctor M. (Frontiers in Immunology, 2018)
Glycogen synthase kinase 3 (GSK3) is a constitutively-active enzyme implicated in the regulation of cytokine expression and the inflammatory response during bacterial infections. Mammals have two GSK3 isoforms named GSK3α and GSK3β that plays different but often overlapping functions. Although the role of GSK3β in cytokine regulation during the inflammatory response caused by bacteria is well described, GSK3α has not been found to participate in this process. Therefore, we tested if GSK3α may act as a regulatory isoform in the cytokine expression by bovine endothelial cells (BEC) infected with Staphylococcus aureus because this bacterium is one of the major pathogens that cause tissue damage associated with inflammatory dysfunction. Interestingly, although both isoforms were phosphorylated-inactivated we consistently observed a higher phosphorylation of GSK3α at Ser21 than GSK3β at Ser9 after bacterial challenge. During a temporal course of infection, we characterized a molecular switch from pro-inflammatory cytokine expression (IL-8), promoted by nuclear factor-kappaB (NF-kB), at an early stage (2 h) to an anti-inflammatory cytokine expression (IL-10), promoted by cAMP-response element binding CREB, at a later stage (6 h). We observed an indirect effect of GSK3α activity on NF-kB activation that resulted in a low phosphorylation of CREB at Ser133, a decreased interaction between CREB and CREB binding protein (CBP), and a lower expression level of IL-10. Gene-silencing of GSK3α and GSK3β with siRNA indicated that GSK3α knock-out promoted the interaction between CREB and CBP that, in turn, increased the expression of IL-10, reduced the interaction of NF-kB with CBP and reduced the expression of IL-8. These results indicate that GSK3α functions as the primary isoform that regulates the expression of IL-10 in endothelial cells infected with S. aureus.